The Routledge companion to theatre and performance - Allain, Paul; Harvie, Jen (London Routledge, 2014)
"What is theatre? What is performance? What connects them and how are they different? How have they been shaped by events, people, companies, practices and ideas in the twentieth century and after? And where are they heading next? The Routledge Companion to Theatre and Performance offers some answers to these big questions. It provides an accessible, informative and engaging intro- duction to important people and companies, events, concepts and practices that have def ined the complementary fields of theatre and performance studies. Three easy-to-use alphabetized sections include more than 140 entries on topics and people ranging from performance artist Marina Abramovito directors Vsevolod Meyerhold and Robert Wilson, the Living Theatre's Paradise Now, the haka, multimedia performance, political protest and visual theatre. Each entry includes important historical and contextual information, extensive cross-referencing, detailed analysis and an annotated bibliography. The Routledge Companion to Theatre and Performance is a perfect reference guide for the keen student and the passionate theatre-goer alike. Paul Allain, Professor of Theatre and Performance at the University of Kent, has published extensively on Jerzy Grotowski, Polish and Russian theatre and intercultural performer training processes. Jen Harvie, Professor of Contemporary Theatre and Performance at Queen Mary, University of London, has published widely on relationships between contemporary performance and cultural identities, including in Theatre & the City (2009) and Fair Play - Art, Performance and Neoliberalism (2013)"--Provided by publisher.
Includes bibliographical references (pages 269-280) and index.
Keywords: Performing arts; Performing arts -- Biography -- Dictionaries